Circulating LECT2 levels in newly diagnosed type 2 diabetes mellitus and their association with metabolic parameters: An observational study. Issue 15 (April 2018) - Zhang, Zhen; Zeng, Huixian; Lin, Jianghong; Hu, Yinghui; Yang, Rui; Sun, Jia; Chen, Rongping; Chen, Hong
Abstract : Abstract: Leukocyte cell-derived chemotaxin 2 (LECT2) is a hepatokine expressed in hepatocytes and appears to be involved in energy metabolism. The aim of this study was to determine plasma LECT2 levels in newly diagnosed type 2 diabetic patients and to correlate the results with various metabolic parameters. A total of 93 newly diagnosed type 2 diabetic patients and 80 age- and sex-matched nondiabetes mellitus ones were enrolled in the study. Plasma LECT2 levels were measured by enzyme-linked immunosorbent assay. Circulating LECT2 levels were approximately 1.3 times higher in newly diagnosed type 2 diabetic patients than in controls (mean 30.30 vs 23.23 ng/mL, P < .001). Correlation analysis showed that LECT2 was negatively associated with high-density lipoprotein-cholesterol (HDL-C) levels in type 2 diabetic patients and obese subjects ( P < .05). In multiple stepwise regression analysis, HDL-C, HOMA-IR, BMI, FINS, and TG were significantly independent determinants for LECT2 ( P < .05). Our study showed that circulating LECT2 concentrations are significantly higher in newly diagnosed type 2 diabetic patients and further elevated in obese type 2 diabetic patients. LECT2 concentrations are significantly negatively associated with HDL-cholesterol levels in newly diagnosed type 2 diabetic patients and obese subjects.